A Study to Assess the Knowledge Regarding Breast Cancer Screening Programs among Women Attending Selected Outpatient Department of TMM Hospital, Thiruvalla - Joseph, Manju; Manjima, M. J.; Chacko, Anju Treesa; Renjith, Esther; Varghese, Georgeena; Anna Jose, Jemima; Nazrin, S.; Roy, Neha; Mariam Varghese, Rebekah; Siji, R. (International Journal of Nursing Research, 2024)
Background: This study examined the awareness of women visiting TMM Hospital, Thiruvalla’s outpatient department (OPD) regarding breast cancer screening programs. Methods: Quantitative research was used in this study. Survey research is used in this study. The study is conducted in hospitals. Selected ENT, Ortho, Dental, Cardiac, and Neuro OPDs of TMM Hospital in Thiruvalla were investigated. The population is 30 women. The study sample included 30 women. A suitable non-probability sampling method is used. Results: The results show that eight (26.6%) of the thirty samples are 35–40 years old, five (16.6%) are 41–45, eight (26.6%) are 46–50, and nine (30%) are 51–55. Regarding education, eleven samples (36.6%) completed high school, two (6.6%) completed higher secondary education, two (6.6%) completed a diploma program, eleven (36.6%) completed graduate school, and four (13.3%) completed postgraduate studies. In this study, 7 (23.3%) are professionals, 21 (70%) are housewives, and 2 (6.6%) are unemployed. Twelve (40%) of the thirty samples have a household income of <10,000, eight (26.6%) between 10,000 and 20,000, two (6.6%) between 20,000 and 30,000, and eight (26.6%) over 30,000. Fourteen (46.6%) of thirty samples had good knowledge of breast cancer screening programs, nine (30%) had outstanding knowledge, and seven (23.3%) had moderate knowledge. Conclusions: Knowledge of breast cancer screening programs is linked to education, occupation, and breastfeeding duration. Knowledge of breast cancer screening programs is unrelated to demographic factors like age. The study identified a need for breast cancer education.